Employment Hardship Among Older Workers: Does Residential and Gender Inequality Extend Into Older Age? - Slack, Tim (J Gerontol B Psychol Sci Soc Sci, 2008)
Objectives. The realities of a rapidly aging society make the employment circumstances of older workers an increasingly important social issue. We examine the prevalence and correlates of underemployment among older Americans, with a special focus on residence and gender, to provide an assessment of the labor market challenges facing older workers. Methods. We analyzed data from the March Current Population Surveys for the years 2003, 2004, and 2005. We used descriptive statistics to explore the prevalence of underemployment among older workers and developed multivariate models to assess the impact of age, residence, and gender on the likelihood of underemployment, net of other predictors. Results. We found clear disadvantages for older workers relative to their middle-aged counterparts, and particular disadvantages for older rural residents and women. Multivariate models showed that the disadvantages of older age held net of other predictors. The results also indicated that much of the disadvantage faced by older rural workers and women was explained by factors other than age, particularly education. Discussion. In an aging society, underemployment among older workers comes at an increasing social cost. Policies aimed at supporting older workers and alleviating employment hardship among them are increasingly in the public interest.